Association between visceral fat and influenza infection in Japanese adults: A population-based cross-sectional study. - Keita Kinoshita; Naoki Ozato; Tohru Yamaguchi; Kenta Mori; Yoshihisa Katsuragi; Takuji Yasukawa; Koichi Murashita; Shigeyuki Nakaji; Kazushige Ihara (PLoS ONE, 2022)
Background Several studies have reported that obesity is associated with influenza infection; however, the role of visceral fat remains unclear. The aim of this study was to investigate the association between visceral fat and influenza infection in community-dwelling Japanese adults. Methods A cross-sectional study was performed using data from an annual community-based health check-up conducted from May to June in 2019. In total, 1,040 Japanese adults aged 20-89 years were enrolled in this study. Influenza infection status was determined by participants' responses to a self-administered questionnaire. The visceral fat area (VFA) was measured using a bioimpedance-type visceral fat meter. Participants were classified into four groups using the following cut-off points: VFA < 100 cm2 was set as the reference category according to the Japanese criteria, 100 ≤ VFA < 150 cm2, 150 ≤ VFA < 200 cm2, and 200 cm2 ≤ VFA. Logistic regression models were used to assess the association between VFA and influenza infection. Results In total, 119 participants had influenza infections in the past year. In the multivariate adjusted model, a higher VFA was significantly associated with increased influenza infection; the adjusted odds ratio for 200 cm2 ≤ VFA was 5.03 [95% confidence interval (CI): 1.07-23.6], that for 150 ≤ VFA < 200 cm2 was 1.97 (95% CI: 0.71-5.45), and that for 100 ≤ VFA < 150 cm2 was 1.62 (95% CI: 0.84-3.12), compared with that for VFA < 100 cm2 (p for trend = 0.049). These findings were confirmed in the same cohort the following year. Conclusions Our results suggest that visceral fat accumulation is associated with influenza infection. Large-scale prospective studies using diagnostic information for influenza infection are required to confirm this association.